A genome‐wide association study for reading and language abilities in two population cohorts. (20th June 2013) - Luciano, M.; Evans, D. M.; Hansell, N. K.; Medland, S. E.; Montgomery, G. W.; Martin, N. G.; Wright, M. J.; Bates, T. C.
Abstract : Candidate genes have been identified for both reading and language, but most of the heritable variance in these traits remains unexplained. Here, we report a genome‐wide association meta‐analysis of two large cohorts: population samples of Australian twins and siblings aged 12–25 years ( n = 1177 from 538 families), and a younger cohort of children of the UK Avon Longitudinal Study of Parents and their Children (aged 8 and 9 years; maximum n = 5472). Suggestive association was indicated for reading measures and non‐word repetition (NWR), with the greatest support found for single nucleotide polymorphisms (SNPs) in the pseudogene, ABCC13 ( P = 7.34 × 10 −8 ), and the gene, DAZAP1 ( P = 1.32 × 10 −6 ). Gene‐based analyses showed significant association ( P < 2.8 × 10 −6 ) for reading and spelling with genes CD2L1, CDC2L2 and RCAN3 in two loci on chromosome 1. Some support was found for the same SNPs having effects on both reading skill and NWR, which is compatible with behavior genetic evidence for influences of reading acquisition on phonological‐task performance. The results implicate novel candidates for study in additional cohorts for reading and language abilities. Abstract : Genome‐wide association analysis implicates loci involved in reading and language skills in the general population.